2022
DOI: 10.3390/molecules27248807
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Isatin-Tethered Quinolines as Anti-Tubercular Agents against Multi and Extensively Drug-Resistant Mycobacterium tuberculosis

Abstract: We describe the design and synthesis of two isatin-tethered quinolines series (Q6a–h and Q8a–h), in connection with our research interest in developing novel isatin-bearing anti-tubercular candidates. In a previous study, a series of small molecules bearing a quinoline-3-carbohydrazone moiety was developed as anti-tubercular agents, and compound IV disclosed the highest potency with MIC value equal to 6.24 µg/mL. In the current work, we adopted the bioisosteric replacement approach to replace the 3,4,5-trimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In Fig. 1 , a previous studies have shown that structural modification at different positions of isatin makes it possible to improve its pharmacological properties, conferring it antitubercular [ 39 , 40 ], antimalarial [ [41] , [42] , [43] ], anticonvulsant [ [44] , [45] , [46] ] antimicrobial [ [47] , [48] , [49] ], anticancer [ 50 , 51 ], antidiabetic [ [52] , [53] , [54] , [55] ] and anti-HIV [ [56] , [57] , [58] ] properties as well as CDK2 (cyclin-dependent kinase 2) inhibitors [ 59 , 60 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 1 , a previous studies have shown that structural modification at different positions of isatin makes it possible to improve its pharmacological properties, conferring it antitubercular [ 39 , 40 ], antimalarial [ [41] , [42] , [43] ], anticonvulsant [ [44] , [45] , [46] ] antimicrobial [ [47] , [48] , [49] ], anticancer [ 50 , 51 ], antidiabetic [ [52] , [53] , [54] , [55] ] and anti-HIV [ [56] , [57] , [58] ] properties as well as CDK2 (cyclin-dependent kinase 2) inhibitors [ 59 , 60 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The unique structure of quinoline contributes to its interaction with biological systems, leading to its use in medicinal chemistry [7,8]. Quinoline and its derivatives have been employed in the synthesis of drugs with antimalarial [9,10], antitubercular [11,12], antitumor [13,14], antibacterial, and antifungal activities [15,16]. The nitrogen atom in the quinoline ring can serve as a coordination center for metal ions, a property exploited in many aspects of coordination chemistry [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compound II was the most potent derivative of the isatin–quinoline hybrids that we reported and assessed formerly for their antimycobacterial activity. [ 22 ] Its MIC equals 0.06 µg/mL, which is considered an excellent hit to be further optimized.…”
Section: Introductionmentioning
confidence: 99%